Performance Evaluation of Construction Waste Management through a Sustainable Development Approach (Case Study: Green Plesungan Housing Project Development) - Abdullah, Muhammad Ma'mun Harits; Solikin, Mochamad; Mutiari, Dhani; Harnaeni, Senja Rum (ASTONJADRO, 2026)
The continuous growth of infrastructure development in Indonesia has led to a significant increase in construction waste, impacting project costs and environmental sustainability. This study aims to evaluate the performance of construction waste management using a sustainable development approach in the Green Plesungan Housing Project. The research employed a quantitative approach through site observations, technical data collection, and questionnaire distribution to 30 construction stakeholders. The evaluation began with the calculation of waste materials, waste levels, and waste costs, followed by statistical analyses including instrument testing, classical assumption testing, multiple linear regression, simultaneous and partial tests, the coefficient of determination test, as well as the formulation of recommended steps to minimize waste. The study identified 16 types of construction waste, with structural works being the largest contributors. The total waste cost reached 3.48% of the material contract value of Rp. 33,617,860.77, with lightweight bricks contributing the highest cost at 1.06%, amounting to Rp. 10,275,739.37. Statistical results indicated that six out of seven variables significantly influenced the implementation of sustainable practices, with a contribution of 95.4%. Site supervision, on-site execution, and environmental conditions were identified as the dominant factors contributing to waste production. The proposed strategies to minimize waste include enhancing planning accuracy, improving logistics management, promoting disciplined and efficient execution, and strengthening site supervision. This study provides valuable insights for developing integrated construction waste management strategies that not only reduce waste costs but also support the realization of sustainable and efficient housing development in the future.